Synthesis and properties of donor/acceptor-substituted metal-capped twofold-sila-bridged cyclobutadieno superphanes - Schaller, Rolf; Haberhauer, Gebhard; Gleiter, Rolf; Rominger, Frank (European journal of inorganic chemistry, 2002)
The synthesis of the tetrasilasuperphanes 10−18 can be achieved from 1,1,3,3-tetramethyl-1,3-disilacyclonona-4,8-diyne (7), 1,1,2,2-tetramethyl-1,2-disilacyclonona-3,8-diyne (8) or 1,1,4,4-tetramethyl-1,4-disilacyclodeca-5,9-diyne (9) by heating with [RCpCoL2] [R = H, Si(CH3)3, (CH3)5, CO2CH3; L2 = COD, (CO)2, (C2H4)2]. The reaction of 7 with [RCpCo(CO)2] [R = H, CH3, Si(CH3)3, (CH3)5] produces the tricyclic cobalt-stabilized cyclobutadienediynes 20−23, whereas reaction with [R′CpCo(L2)] [R′ = H, (CH3)5, CO2CH3; L2 = COD, (CO)2] leads to the donor/acceptor superphanes 24−31. X-ray investigations on the superphanes 10, 13−15 and 18 reveal distances between the two cyclobutadiene units in the range of 2.65 Å and 3.79 Å. Investigations by means of cyclic voltammetry of the superphanes 10−18 show a dependence of the oxidation potentials on the nature of the bridges. A comparison between the first oxidation potentials of 10/28, 24/29, and 26/31 gives evidence for a partial charge delocalization over both CpCoCbd fragments of the superphanes. (© Wiley-VCH Verlag GmbH, 69451 Weinheim, Germany, 2002)
Dedicated to Professor Gottfried Huttner on the occasion of his 65th birthday
Gesehen am 23.10.2020
Keywords: Festschrift